Software, Animation and the Moving Image What's in the Box? - Wood, A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2015)
Software, Animation and the Moving Image brings a unique perspective to the study of computer-generated animation by placing interviews undertaken with animators alongside an analysis of the user interface of animation software. Wood develops a novel framework for considering computer-generated images found in visual effects and animations.
Keywords: Software engineering; Computer organization; Computer graphics; Computer simulation; Engineering; Software Engineering; Computer Systems Organization and Communication Networks; Computer Graphics; Simulation and Modeling; Engineering, general